Health-related quality of life of antiretroviral treatment defaulters in Botswana - Nnamdi O. Ndubuka; Hyun J. Lim; Dirk M. van der Wal; Valerie J. Ehlers (AOSIS, 2016)
Background: Antiretroviral therapy (ART) improves patients' health-related quality of life (HRQoL). Defaulting from ART has detrimental consequences, including the development of viral resistance, treatment failure and increased risks of disease progression. Little is known about the quality of life of ART defaulters and reasons for discontinuing their ART. Objectives: This study sought to measure the HRQoL of ART patients in Botswana who were on ART for up to 5 years but had discontinued treatment for at least 3 months, and to identify factors associated with ART defaulting. Method: We conducted a cross-sectional study with 104 eligible respondents in four ART clinics in south eastern Botswana. We assessed respondents' HRQoL using the World Health Organization Quality of Life Questionnaire for HIV short form. Clinical information was obtained from respondents' medical records. Data were analysed using SAS version 9.2. Results: Reasons for discontinuing ART were inaccessible clinics (22.4%), feeling better (21.4%), running out of pills (11.2%), depression (8.2%), lack of care and/or support (8.2%), failure to understand instructions (7.7%), medications' side effects (6.1%) and alcohol abuse (3.1%). In multivariate analyses, respondents aged 36-45 years had a 0.03 lower independence HRQoL score compared to those aged 35 and younger (β = -0.03; 95% confidence interval: -1.72, -1.66). Despite defaulting from their ART, respondents' calculated HRQoL scores were Conclusion: This study highlights the need to enhance ART adherence in order to improve the HRQoL of people living with HIV and/or AIDS.